RD Lawrence lecture 2012: assessing aetiology in diabetes: how C-peptide, CRP and fucosylation came to the party! - Owen, K (2013)
Assigning the correct aetiology in diabetes is important for treatment, understanding prognosis and for follow-up of family members. Despite these benefits, many are missing out on the opportunity to have testing for monogenic forms of diabetes. This review gives the clinical features of the commoner forms of monogenic diabetes and examines which clinical and biological markers can be used to identify those at highest risk of having Maturity onset diabetes of the young (MODY). MODY is characterised by young-onset, familial diabetes which is C-peptide positive, β-cell antibody negative and not associated with metabolic syndrome. Differentiating from type 1 and type 2 diabetes can be challenging due to the overlap of clinical features. In type 1 diabetes, insulin production ceases after the honeymoon period. Thus C-peptide can be used to detect those with persisting insulin secretion who might have a different cause for their diabetes. In type 2 diabetes, most have insulin resistance, so absence of metabolic syndrome could be used to identify those most likely to have MODY. Another approach is to look for non-pancreatic features associated with mutations in MODY genes. Following results from Genome-wide association studies, we have shown that those with HNF1A mutations (the commonest form of MODY) have decreased serum levels of highly-sensitive C-reactive protein (hsCRP) and altered patterns of plasma protein fucosylation. These features can differentiate HNF1A-MODY from common forms of diabetes with a high degree of discriminative accuracy. Using combinations of clinical features and new biomarkers in diagnostic pathways will help increase diagnosis rates of MODY.